UMA VOZ FEMININA NO SÉCULO XVII: A AUTOBIOGRAFIA DE ANTÓNIA MARGARIDA DE CASTELO BRANCO - Volupca, Paula Aparecida (2015)
The autobiography has been drawing more and more attention of scholars from various subjects/disciplines, as pointed out by Philippe Lejeune: "[...] the autobiography takes us to open ourselves to other subjects, mainly psychoanalysis, psychology, sociology, the story. [...]" (Lejeune, 2008, p. 66). These areas have formed as signaling new directions for the study of the writings themselves, now, over the last time, to be considered as a socio-cultural practice whose historical and contextual dimensions lead the researcher to integrate the elements of other disciplines, in order to formulate their ideas about the topic. In the literature, in particular the memorialistic genre by presenting commitment to truth, encourages the researcher to investigate constituent elements of their context of production and to establish what Lejeune calls "autobiographical pact", thus enabling the recreation of a history moment and its social implications, so that we can illustrate with due property which elements were crucial in the development of a particular work. The objective of this work is the realization of reading of the Autobiography of Antónia Margarida de Castelo Branco (1983) taking into account the interpretative model proposed by Fredric Jameson, proposed in his book O inconsciente político (1992), a reading done against the grain, in others words a reading done beyond what the text brings in its appearance. Other aspects analyzed in this work, are the "containment strategies" and the "manifest content", also from the proposal of Fredric Jameson in the O Inconsciente Político (1992). These strategies deal of what he did not say, for some reason, to produce your text. They treat, according to the theoretical, than not appear in the text of the superficial, but what`s between the lines, that is, the traps used by the author of the work, consciously or unconsciously, to mask certain topics that go beyond the manifest content. It takes into account also some elements of "Aesthetics of Reception" of the Hans Robert Jauss (1994), including the "horizon of expectations" and the "fusion of horizons" in order to realize the effects of work on readers and their permanence over time. Finally, analysis of the Autobiography of Antónia Margarida de Castelo Branco as a literary work of memoirist nature also makes up as the Roberto Schwarz notes in his book Duas meninas (1997).